Study of the zero shear viscosity of SBS copolymer modified bitumens - Słowik, Mieczysław; Andrzejczak, Marta (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper presents the results of the zero shear viscosity (ZSV) determined by using a dynamic shear rheometer (DSR). The tests were conducted with the use of 50/70 penetration grade bitumen produced from Venezuelan and Russian crude oils (named V50/70 and R50/70, respectively). Specimens of the tested polymer modified bitumens were combined with modified bitumen concentrate (containing 9% of SBS copolymer) by mixing them together. The objects of the tests were modified bitumens containing 1.5%; 3.0%; 4.5%; 6.0% and 9.0% of SBS copolymer. Zero shear viscosity (ZSV) was determined with the use of two methods: the creep method at various levels of shear stress in the time sequence and a method in which kinematic, sinusoidal angular deformation was applied. The tests were conducted at a constant temperature of 60˚C. The results of two ZSV tests gave similar findings for 50/70 penetration grade bitumen and modified bitumen with low SBS copolymer content (1.5%). In the case of modified bitumen with higher SBS copolymer content, i.e. 3%; 4.5%; 6%; 9%, zero shear viscosity determined by two methods gave different results.